The Rights of Exclusive Licensee to Sue the Copyright Infringement Case - Sitthisook, Wannakarn (Huachiew Chalermprakiet Law Journal, 2025)
Copyright is a form of intellectual property, and copyright owners have the legal right to authorize others, as licensees, to reproduce, adapt, or publicly distribute their copyrighted works. However, in the event of licensing in Thailand, licensees, particularly exclusive licensees, often face copyright infringement and suffer damages, despite having invested substantial capital and paid significant consideration to obtain exclusive rights within a defined scope. Thai copyright law currently lacks explicit statutory protection for such exclusive licensees, and judicial precedents on the matter remain unclear. This problem serves as the basis for this article, which aims to examine foreign copyright laws in order to propose improvements to Thai copyright legislation. The study found that the copyright laws of the United Kingdom and the United States provide clear legal standing and remedies for exclusive licensees to bring lawsuit against the infringement in their own name. Accordingly, the author proposes two approaches to address the issue of the rights of exclusive licensees to sue the copyright infringement case. The first approach is to apply the principles found in foreign jurisdictions into the revision of the Thai Copyright Act B.E. 2537 (1994). The other is to develop the templates of licensing agreement that explicitly sets forth the licensee’s rights to enforce the copyright and other related rights, thereby preventing future disputes or imbalances between the contracting parties.